Evaluation of Serum Ferritin and CRP Levels in Children with Bacterial Pneumonia - Khansaa Akram Hasan (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Bacterial pneumonia remains a major cause of pediatric morbidity and hospitalization, characterized by systemic inflammatory responses involving acute-phase reactants and iron metabolism. Specific Background: C-reactive protein (CRP) and serum ferritin are recognized inflammatory biomarkers; however, their combined evaluation in pediatric bacterial pneumonia and their association with disease severity and clinical indicators require further clarification. Knowledge Gap: Limited data are available regarding the diagnostic and prognostic relevance of ferritin alongside CRP in children with clinically and radiologically confirmed bacterial pneumonia. Aims: This case–control study aimed to evaluate serum ferritin and CRP levels in 60 children with bacterial pneumonia compared with 40 healthy controls and to determine their relationship with severity classification and clinical parameters. Results: Serum ferritin and CRP levels were significantly higher in pneumonia patients than controls (p < 0.001) and demonstrated a progressive increase from mild to severe cases (p < 0.001). Both biomarkers showed significant positive correlations with body temperature, white blood cell count, and length of hospital stay. Novelty: The study demonstrates a graded rise of ferritin and CRP corresponding to clinical severity categories within a well-defined pediatric cohort. Implications: Combined assessment of ferritin and CRP may support severity stratification, clinical monitoring, and prognostic evaluation in pediatric bacterial pneumonia. Highlights: • Inflammatory Biomarker Concentrations Were Significantly Higher in Affected Children Compared With Matched Healthy Controls.• Progressive Increases Were Observed From Mild to Severe Clinical Classification.• Positive Correlations Were Identified With Fever Intensity, Leukocyte Count, and Hospitalization Duration. Keywords: Bacterial Pneumonia, Serum Ferritin, C Reactive Protein, Pediatric Inflammation, Disease Severity